ICT and Bank Performance: Empirical Evidence from Vietnam - THUY, NGUYEN VAN (The journal of contemporary issues in business and government, 2021)
The development of new information and communication technologies has led to a fundamental transformation of commercial banks currently and in the future. This article studies the impact of ICT on the performance of commercial banks. By using data from 20 Vietnamese commercial banks in the 2007-2019 period and the ICTIndex set of indicators for commercial banks, we see that readiness for IT development and application has had a significant impact on bank performance, among other factors such as the size of the bank, the ratio of equity to total assets and the ratio of deposits to loans.